’Mensen ... worden niet geboren maar gevormd’: Erasmus en het principe van de opvoeding - Herwaarden, J. van (BMGN - Low Countries Historical Review, 2007)
‘People... are not born but formed’: Erasmus and the principle of educating young people In Erasmus’ opinion human beings ware created by God with the propensity for reason that enables them to develop the potential that nature has given them. Breeding and education should be initiated as soon as possible after birth and should focus on making the child think and act independently, within the framework of christian pietas. Language and letters - the bonae litterae - were indispendable instruments for what was named the studia humanitatis, which moulded people into citizens of the world, marked by an acute awareness of their obligations to the Christian community. This article is part of the special issue ’De menselijke canon en de Lage Landen’.